Governance Innovation and Public Service Effectiveness at the Sub-district Level: A Contextual Qualitative Analysis - Robin Pakudu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study analyzes the effectiveness, efficiency, and fairness of public services at the sub-district level in the context of fiscal constraints and institutional capacity. Using a descriptive qualitative research design combined with thematic and spatial analysis, this study assesses how governance innovations, institutional capacity, and basic infrastructure affect public service performance. Data were collected through multiactor interviews, observations, and document analysis involving 45 respondents from three administrative clusters. Results indicate that prioritizing basic needs such as road repairs, clean water access, and public lighting significantly improves public service accessibility and satisfaction, even under budget constraints. Data-driven governance innovations and digital technology increase service efficiency by approximately 35% and strengthen budget accountability. Program sustainability is strongly influenced by cross-period political commitment, staff training, and the existence of a transparent audit trail. Infrastructure quality is positively related to citizen satisfaction (r = 0.72), but maximum impact is achieved when supported by strong human resource capacity and information technology. The integration of public participation and transparency within the New Public Service framework has been shown to strengthen service fairness and responsiveness. This research provides empirical contributions to the development of a sustainable local governance model based on innovation and basic needs, and recommends further research on the integration of spatial and digital indicators in public policy evaluation in rural areas.